Factors affecting fluorescent intensity of Fe3O4-cyanine 5.5 nanoparticles - Huong, Le Thi Thu; Ke, Phan Ke; Thuy, Ung Thi Dieu; Anh, Tran Thi Lan; Nham, Dong Thi; Thu, Ha Phuong (Vietnam Journal of Science and Technology, 2022)
In the diagnosis and treatment of cancer, the nano drug delivery systems have been intensively researched for many years because they are capable of concentrating drugs at the target for a longer time, while protecting other tissues in the body. Recently, fluorescent-magnetic nanomaterials have attracted much attention from researchers in biomedicine due to these multifunctional nanomaterials have great prospects for application in multimodal biomedical imaging in combination with chemotherapy and hyperthermia. However, the factors affecting fluorescent intensity of fluorescent magnetic nanomaterials have not been investigated. In this study, we examined the dependence of fluorescent intensity on different factors in the synthesis process of Fe3O4-cyanine 5.5 nanoparticles. The results showed that Fe3O4 nanoparticles needed to be covered with a layer of NH2 group before reacting with cyanine 5.5-NHS ester. The best cyanine 5.5 NHS ester : Fe3O4 and cyanine 5.5 NHS ester : APTES ratios were 1 : 20 and 1 : 3, respectively. The drug delivery did not affect much the fluorescent property while increasing the excitation wavelength could lead to an increase in the fluorescent intensity of the system. These results are the basis to continue to evaluate the potential of Fe3O4-cyanine 5.5 nanoparticles in further in vitro and in vivo biological tests.